RETRACTED: Podophyllotoxin and Rutin Modulate M1 (iNOS+) Macrophages and Mitigate Lethal Radiation (LR) Induced Inflammatory Responses in Mice - Nadella, Vinod; Ranjan, Rajiv; Senthilkumaran, Balasubramanian; Qadri, S. S. Y. H.; Pothani, Suresh; Singh, Ajay Kumar; Gupta, Manju L.; Prakash, Hridayesh (Frontiers in Immunology, 2019)
Accidental exposure to lethal doses of Gamma radiation leads to the systemic inflammatory syndrome which causes mortality. In view of this, management of hemopoietic syndrome by modulating pro-inflammatory response in clinically manageable time period seems to be the most appropriate strategy for encountering radiation induced damage and recovery. As both tissue and peripheral macrophages are critical for the management of radiation induced injuries, we have unravelled the immunomodulatory potential of radioprotective formulation (G-003M)on peripheral macrophages populations in this study. G-003M inhibited lethal radiation induced NO and Th1 effector cytokines in the exposed macrophages indicating its M1 dim polarizing capacity.In similar lines, conditioning of mice with G-003M before lethal irradiation (LR) inhibited LR induced titre of Th1 effector cytokines in both serums as well as in lung, small intestine, and spleen tissue confirming its immunomodulatory potential. G-003M potentially down modulated inflammatory response in LPS induced inflammatory model and enhanced M2 polarization of iNOS+ M1 effector macrophages providing a molecular hint on G-003M mechanism of action on macrophages. These observations revealed that G-003M potentially modulate pro-inflammatory programming of macrophages and mitigate radiation-induced inflammatory stress which is believedto contribute significantly to radioprotective attribute of G-003M.